Emoji Identification and Emoji Effects on Sentence Emotionality in ASD-Diagnosed Adults and Neurotypical Controls. - Hand, Christopher J.; Kennedy, Ashley; Filik, Ruth; Pitchford, Melanie; Robus, Christopher M. (Journal of Autism & Developmental Disorders, 2023)
We investigated ASD-diagnosed adults' and neurotypical (NT) controls' processing of emoji and emoji influence on the emotionality of otherwise-neutral sentences. Study 1 participants categorised emoji representing the six basic emotions using a fixed-set of emotional adjectives. Results showed that ASD-diagnosed participants' classifications of fearful, sad, and surprised emoji were more diverse and less 'typical' than NT controls' responses. Study 2 participants read emotionally-neutral sentences; half paired with sentence-final happy emoji, half with sad emoji. Participants rated sentence + emoji stimuli for emotional valence. ASD-diagnosed and NT participants rated sentences + happy emoji as equally-positive, however, ASD-diagnosed participants rated sentences + sad emoji as more-negative than NT participants. We must acknowledge differential perceptions and effects of emoji, and emoji-text inter-relationships, when working with neurodiverse stakeholders.